Pharmacology in nursing - Bergersen,B.S (Saint Louis The C.V.Mosyb)
This book focuses on the use of drugs as medications within the healthcare environment in Australia and New Zealand. This text is a resource for nurses and health professionals to assist in their understanding drugs and their actions, especially with regard to the responsibilities of nurses in relation to medication administration and patient management.
Keywords: Pharmacology; Pharmacology; Drugs; Drugs; Nursing; Nursing